STRUCTURING PROCESS AND EVALUATION OF GROUP WORK BY PROSPECTIVE PRE-SCHOOL TEACHERS - Acar-Erdol, Tuba; Öngören, Sema (International Online Journal of Education and Teaching, 2020)
In this study, it was aimed to examine the prospective teachers’ preferences regarding group work, the process of structuring the group work, and assessment of their performance within the group. In the research, case study design was used. The participants of the study consisted of 62 prospective teachers studying in the Department of Early Childhood Education at a state university in 2017-2018 Spring Term. The data of the study were collected with the "Group Work Questionnaire". While frequency analysis of descriptive statistics was used in the analysis of the quantitative data obtained from the questionnaire, descriptive analysis was used in the analysis of the qualitative data. As a result of the research, it was seen that the internal reasons were determinant in deciding the groupmate and tasks were shared by taking equal distribution of responsibilities and skills of the members into consideration. During the group work, problems such as time management, disagreements among members and social loafing were encountered. As to assessment of the performance within the group, it was determined that the group members found themselves competent and that the majority could prefer group work in future studies. Keywords: group work, ingroup performance, prospective teachers, social interaction, social loafing